Implementasi Total Quality Management (TQM) dan Penjaminan Mutu Pendidikan di SMA Muhammadiyah 1 Klaten Kabupaten Klaten Tahun Pelajaran 2014/2015 - Burhanuddin, A (2016)
This Research aim to observe about : 1) The planning of Total Quality Management (TQM) and the Education Quality Assurance at SMA Muhammadiyah 1 Klaten Kabupaten Klaten, 2) the implementation of Total Quality Management (TQM) and the Education Quality Assurance at SMA Muhammadiyah 1 Klaten Kabupaten Klaten, 3) The obstacles found in the implementation of Total Quality Management (TQM) and the Education Quality Assurance at SMA Muhammadiyah 1 Klaten Kabupaten Klaten. This research is using the qualitative study method.This method is applying the interactive mode analysis which consisting of 3 basic components namely the reduction of the data, the exposure of the data and the conclusion. Data sources of this research is the informants and the documents. This research uses the ethnography approach. This research applies the involved observation, interview, and documentation to collect the data. While to examine the validity of the data, this research is considering some important things including the participation, earnestness observation, triangulation, peer examination through dialogue and discussion, the sufficiency references, a case report negative and checks on internal customers. Based on the data analysis and the discussion that has been writer done, it can be conclude, as the follows: 1) The planning of Total Quality Management (TQM) and the Education Quality Assurance at SMA Muhammadiyah 1 Klaten Kabupaten Klaten by taking some steps as follows: a) formed a team to formulate both the model and the systems which will be developed for the implementation Total Quality Management (TQM) and the Education Quality Assurance, b) the service improving, c) identifying and improving the functions of the quality of schools management by considering on the minimum service standard based on the national education standards (SNP) in order to maintain the quality of the school, 2) the implementation of Total Quality Management TQM and the Education Quality Assurance at SMA Muhammadiyah 1 Klaten Kabupaten Klaten is using the bottom up system and open management of school. The education quality assurace at SMA Muhammadiyah 1 Klaten Kabupaten Klaten have met with the service standards in accordance with the government regulation PP no.19, 2005, the pattern of quality assurance which developed is hand in hand with PDCA cycle approach includes the Plan, Do, Check, and Action, 3) the obstacles found in the implementation of the Total Quality Management (TQM) and the Education Quality Assurance at SMA Muhammadiyah 1 Klaten Kabupaten Klaten are: a) the competition in recruitment of students, b) the awareness of some of the teachers and the staff forward in understanding about quality management are weak, c) the management which is applied at SMA Muhammadiyah 1 Klaten Kabupaten Klaten can not be accepted by all the part of the management yet, d) the documentation system on the quality assurance done by the team of the school quality assurance is still weak. Keywords: Implementation, Total Quality Management (TQM), The Education Quality Assurance